Design of a New Cryptosystem Combining a MEMS-Accelerometer and a Chaotic Map - García Bosque, Miguel; Pérez, Adrián; Sánchez-Azqueta, Carlos; Celma, Santiago (Jornada de Jóvenes Investigadores del I3A, 2017)
In this work, we have used a new concept of sensor-based seed generator in order to generate the keys for a stream cipher based on Skew Tent Map and a Linear Feedback Shift Register. The cryptosystem has been implemented in a Xilinx Virtex 7 FPGA VC707 Evaluation Kit and has been proven to be fast and secure.